Maize/soybean intercropping facilitated phosphorus solubilization via shifted and synergistic arbuscular mycorrhizal fungal and bacterial communities in red soil - Qian, Ling; Tang, Li; Xiao, Jingxiu; Mao, Lili; Lv, Ping; Zhang, Faming; Zheng, Yi (Frontiers in Plant Science, 2025)
IntroductionArbuscular mycorrhizal fungi (AMF) are key regulators of phosphorus (P) cycling in agricultural systems. However, under intercropping conditions, the mechanisms through which AMF hyphae and spores recruit specific bacterial taxa and synergistically solubilize insoluble P in red soils remain poorly understood.MethodsThrough a greenhouse pot experiment, we investigated how the symbiotic relationship between AMF and crops varies across a gradient of P fertilizer levels (P0 to P250). We aimed to identify the P level that optimizes this symbiosis and to elucidate, via high-throughput sequencing and network analysis, the regulatory mechanism by which interactions between AMF and phosphate-solubilizing bacteria (PSB) drive P solubilization.ResultsMycorrhizal colonization rate, hyphal length density (HLD), and spore density (SD) exhibited a hump-shaped response to increasing P fertilizer inputs, peaking at P150. IMS enhanced these parameters and also enriched the AMF taxon Glomus_f_Glomeraceae and eight key bacterial genera (e.g., Sphingomonas, Unclassified_f_Micrococcaceae, and Streptomyces). The relative abundance of Glomus_f_Glomeraceae was highest at P150, corresponding to the strongest AMF-crop symbiosis. Network analysis revealed a higher proportion of positive associations between AMF and bacteria in IMS than in monoculture.DiscussionOur findings demonstrate that IMS facilitates P solubilization in red soil by shifting the AMF and bacterial communities toward a more synergistic state. Furthermore, our results provide a mechanistic understanding of how optimized P management in IMS can enhance AMF and bacterial cooperation to improve P use efficiency. These insights offer novel strategies for mycorrhizal function conservation and sustainable agroecosystem management.